(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This scientific article examines the theoretical foundations, practical approaches, and architectural-urban planning solutions aimed at ensuring ecological balance in urban environments. In the face of accelerating urbanization, climate change, and increasing anthropogenic pressures, ensuring ecological equilibrium through architectural interventions has become an urgent necessity. The study focuses on the integration of green infrastructure, bioclimatic design, ecological zoning, blue-green corridors, passive environmental control systems, and ecosystem services into urban planning and architectural practice. A comprehensive methodological framework is applied, combining spatial analysis, environmental modeling, case study comparison, and socio-economic evaluation, using data from Tashkent, Andijan, and Samarkand. The results demonstrate that architectural-urban planning solutions designed with ecological principles can significantly reduce the ecological footprint of cities, enhance urban resilience, improve air and water quality, and support biodiversity. The article concludes that embedding ecological balance strategies within urban planning is essential for sustainable development, climate adaptation, and improved urban livability.